Chemical castration as a penal instrument: An analysis of the Mojokerto district court decision from a human rights perspective - Salsabilla, Atsyilla (The International Journal of Politics and Sociology Research, 2026)
Chemical castration was introduced into Indonesia’s criminal justice system as a legislative response to the increasing prevalence of sexual violence against children. This penal instrument is designed to deter offenders while safeguarding victims’ rights and welfare. One notable application of this sanction can be found in the Mojokerto District Court Decision No. 69/Pid.Sus/2019/PN.Mjk, where chemical castration was imposed as an additional punishment for the perpetrator of child sexual assault. Although grounded in positive law, the implementation of chemical castration raises profound debates within the human rights discourse, particularly regarding the prohibition of torture, the right to bodily integrity, and the protection of human dignity. This study aims to analyze chemical castration as a penal instrument through a normative legal approach, examining the Mojokerto District Court decision from a human rights perspective. Using a juridical-normative method that combines statutory and case approaches, this research finds that chemical castration generates significant tension between the objectives of punishment and the fundamental principles of human rights. Consequently, its application necessitates critical evaluation to ensure alignment with the rule of law, proportionality, and respect for human dignity.